External and Internal Threats in the Process Financial and Economic Monitoring Activity of Enterprise - Полозова, Т. В.; Халіна, В. М. (Pegasus Publishing, 2015)
In article essence financial and economic monitoring is determined, purpose financial and economic monitoring is determined, groups factor influences upon activity of the enterprise are determined, forming threats (external and internal) in process financial and economic monitoring to activity of the enterprise are classified, actions upon their localizations are offered. У статті визначено сутність фінансово-економічного моніторингу, визначена мета фінансово-економічного моніторингу, визначені групи факторів впливу на діяльність підприємства, визначені складові загроз (зовнішніх та внутрішніх) в процесі фінансово-економічного моніторингу діяльності підприємства, запропоновано заходи їх локалізації.
Зовнішні та внутрішні загрози в процесі фінансово-економічного моніторингу діяльності підприємства
Keywords: financial and economic monitoring; categorization of the threats; external and internal factors; localization of the threats; фінансово-економічний моніторинг; класифікація загроз; зовнішні і внутрішні фактори; локалізація загроз